Social Media for Leaders Your team can steer the boat but you need chart the course - Babka, Stefanie (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer, 2023)
This book provides you with a concise and accurate overview of the key business challenges, opportunities and risks related to social media. Regardless of the type and size of company or department you manage, whether you offer industrial goods, consumer goods or services - social media is a factor you should monitor and manage. Stefanie Babka helps you ask yourself and your employees the right questions, find answers and thus face the internal challenges. Because social media is a management task. For example, the following questions are highlighted: Are you aware of the risks of uncoordinated and improper use of social media by your employees in their private or professional lives? Have you taken everything into account in terms of data protection law, or do you already have one foot in jail as a manager? Are you spending too much money on social media campaigns? Do you have the right social media strategy? Is it aligned with your company's goals? Are you in control or does social media anarchy reign in your company? What opportunities and risks do internal social media applications bring for collaboration in teams or organizational units? How can social media be used as a strategic management tool? Social media concerns every company. Whether you like it or not. For the 2nd edition, all contents have been revised and the chapter "As a manager on the social web" has been expanded to include, among other things, the topic of virtual management and leading virtual teams. The content The internal organization of social media in the company The path to the right social media strategy Social media in the various corporate departments Opportunities and risks for your company and for you as a manager Social media as a leadership tool and virtual management The author Stefanie Babka has more than 15 years of experience in digital and social media within several large corporations (Daimler, GM, Nestlé, Merck) and has experience in leading employees and interdisciplinary teams as well as transformation projects in a global context. She has won several prestigious awards with corporate projects such as the "German Prize for Online Communication" or the "Enterprise Business Collaboration Award". As a speaker, she regularly appears at international conferences on topics such as the digital workplace, social media and female leadership. This book is a translation of an original German edition. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation.
Public Relations -- Marketing -- Human Resources -- Internal Communications -- Purchasing -- Compliance -- Legal/Data Privacy -- Sales -- Finance/Controlling -- Corporate Security -- Research and Development -- Production -- Customer Service/Service -- Works Council -- Quality Assurance -- IT -- Investor Relations -- Other External Stakeholders.
Keywords: Telemarketing; Internet marketing; Social media; Digital Marketing; Social Media